“Cimmerian” bridles from a barrow near Slobozia (Lower Dniester Region) - Stepanova Elena V.; Kashuba Maya T. (Поволжская археология)
A new study of the burial inventory from the early nomadic (“Cimmerian”) burial 3 barrow 3 Slobozia from the Lower Dniester region (the western flank of the “Great Steppe Belt”) allowed us to clarify the number of elements of bridle and its decoration found in the burial by category of finds. The analysis revealed that the burial contained details of at least five sets of bridles; for some of them were used round in section belts and for the others – the flat ones. The bridle features caused differences in their decoration. Two versions of the reconstruction of the bridles made of round and flat belts were created. New observations confirm that barrow 3 of Slobozia was made for the burial of a mounted warrior of high social status (burial 3). The second pre-Scythian (“Cimmerian”) burial in the mound (burial 1) indicates that this barrow was specially marked and could be recognized by the early nomads of the region as “theirs” (“ancestral grave”).